How do collective student behavior and other classroom contextual factors relate to teachers' implementation of an evidence-based intervention? A multilevel structural equation model. (December 2019) - Musci, Rashelle J.; Pas, Elise T.; Bettencourt, Amie F.; Masyn, Katherine E.; Ialongo, Nicholas S.; Bradshaw, Catherine P.
Abstract: Building on prior work regarding the potential for peer contagion or deviance training in group delivered interventions (Dishion & Dodge, 2005, 2006; Dodge, Dishion, & Lansford, 2006), we leveraged data from a randomized trial, testing the integration of two preventive interventions (Promoting Alternative THinking Strategies and PAX Good Behavior Game), to explore the extent to which classroom contextual factors served as either a barrier to or a motivator for teachers to implement the evidence-based PAX Good Behavior Game with high frequency or dosage. We included students' baseline levels of behavior, measured with regard to both positive (i.e., engagement and social emotional skills) and negative (i.e., hyperactive and aggressive-disruptive) behaviors. Data were collected from 204 teachers in 18 urban elementary schools. A series of multilevel structural equation models were fit to the data. The analyses indicated that classrooms with higher classroom levels of aggressive behavior, on average, at baseline had teachers with lower implementation dosage (i.e., played fewer games) across the school year. In addition, teachers who reported higher baseline levels of emotional exhaustion, regardless of student behavior, also reported lower implementation dosage. Taken together, the results indicated that negative, but not positive, contextual factors at baseline were related to lower implementation dosage; this, in turn, suggests that negative contextual factors may serve as a barrier, rather than a motivator, of teachers' implementation dosage of classroom-based preventive interventions.